Pelatihan Pembuatan Pakan Awetan Jerami Fermentasi di Kelompok Tani Bola Buhung Kabupaten Maros - Haerul, Haerul; Risal, Muhammad; Mirnawati, Mirnawati (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The scarcity of cattle feed in certain months causes low livestock productivity. Providing only fresh straw as feed is not enough to meet the need for quality and sustainable feed because the short rice harvest period, resulting in a lot of straw left in the fields and unused. The purpose of this community service activity is to improve farmers' knowledge and skills in managing and utilizing rice crop waste in the form of straw into preserved feed. The activity was carried out on July 25, 2025, at the land of the head of the Bola Buhung farmer group in Limapoccoe Village, Cenrana District, Maros Regency. The implementation of the training activity began with socialization and counseling regarding the potential use of rice straw into quality and long-lasting preserved feed and the stages of its manufacture. Next, training and demonstrations were conducted on making fermented straw preserved feed. The training successfully increased 58.5% of farmers' understanding of the technique of making fermented straw as preserved feed for cattle from 39% to 98.75%. Increasing farmers' knowledge in processing rice straw into preserved feed with a better digestibility level is expected to meet the current shortage of livestock feed, while also realizing integrated livestock and rice farming to support food self-sufficiency in Limapoccoe Village.